Integration of transparent insulation shells in linear solar receivers for enhanced energy and exergy performances. (June 2021) - Amein, Hamza; Kassem, Mahmoud A.; Ali, Shady; Hassan, Muhammed A.
Abstract: This study investigates the performance enhancement of parabolic trough concentrators (PTCs) with transparent insulation material shell (TIMS) of different diameters and thicknesses integrated into evacuated and non-evacuated heat collection elements (HCEs). The results show that non-evacuated TIMS-HCEs have higher energy and exergy efficiencies by up to 62.4 and 63.2%, compared to conventional evacuated HCEs, and by up to 109.2 and 110.9%, compared to conventional non-evacuated HCEs. At high flow rates and low fluid temperatures, the energetic performance of a conventional evacuated HCE is only 6.3% higher than that of the modified non-evacuated one. The modified design also enhances the circumferential temperature uniformity and shows a marginal drop in efficiency when the vacuum is lost. By simulating the PTC performance during four typical days, and without vacuum, the proposed design increased the daily useful heat gain by up to 1.36 and 5.64 kWh, compared to conventional evacuated and non-evacuated HCEs, respectively. Hence, it is proposed as a low-tech alternative to HCE evacuation and as a method of boosting the performance of PTCs operating at low flow rates and high temperatures. Graphical abstract: Image 1 Highlights: Receiver of parabolic trough collector is enhanced using transparent insulation. An MCRT-FVM model is developed for evaluating conventional and modified designs. Without vacuum, the modified design outperforms a conventional evacuated one. Energy and exergy efficiencies are enhanced by up to 62.4 and 63.2%, respectively. The modified design shows better temperature uniformity with no consumed power.